Cell Wall Proteomics Reveal Phenotypic Adaption of Drug-Resistant Mycobacterium smegmatis to Subinhibitory Rifampicin Exposure - Giddey, Alexander D.; Ganief, Tariq A.; Ganief, Naadir; Koch, Anastasia; Warner, Digby F.; Soares, Nelson C.; Blackburn, Jonathan M. (Frontiers in Medicine, 2021)
Despite the availability of effective drug treatment, Mycobacterium tuberculosis (Mtb), the causative agent of TB disease, kills 1. 5 million people annually, and the rising prevalence of drug resistance increasingly threatens to worsen this plight. We previously showed that sublethal exposure to the frontline anti-TB drug, rifampicin, resulted in substantial adaptive remodeling of the proteome of the model organism, Mycobacterium smegmatis, in the drug-sensitive mc2155 strain [wild type (WT)]. In this study, we investigate whether these responses are conserved in an engineered, isogenic mutant harboring the clinically relevant S531L rifampicin resistance-conferring mutation (SL) and distinguish the responses that are specific to RNA polymerase β subunit- (RpoB-) binding activity of rifampicin from those that are dependent on the presence of rifampicin alone. We verified the drug resistance status of this strain and observed no phenotypic indications of rifampicin-induced stress upon treatment with the same concentration as used in WT (2.5 μg/ml). Thereafter, we used a cell wall-enrichment strategy to focus attention on the cell wall proteome and observed 253 proteins to be dysregulated in SL bacteria in comparison with 716 proteins in WT. We observed that decreased abundance of ATP-binding cassette (ABC) transporters and increased abundance of ribosomal machinery were conserved in the SL strain, whereas the upregulation of transcriptional machinery and the downregulation of numerous two-component systems were not. We conclude that the drug-resistant M. smegmatis strain displays some of the same proteomic responses observed in WT and suggest that this evidence supports the hypothesis that rifampicin exercises effects beyond RpoB-interaction alone and that mycobacteria recognise rifampicin as a signaling molecule in an RpoB-independent manner at sublethal doses. Taken together, our data indicates mixed RpoB-independent and RpoB-dependent proteomic remodeling in WT mycobacteria, with evidence for RpoB-independent ABC transporter downregulation, but drug activity-based transcriptional upregulation and two-component system downregulation.